THE EARLY VENDIAN MICROFOSSILS FIRST FOUND IN THE RUSSIAN PLATE: TAXONOMIC COMPOSITION AND BIOSTRATIGRAPHIC SIGNIFICANCE - Veis A.F.; Vorob'eva N.G.; Golubkova E.Yu. (My University, 2006)
The microfossils studied are discovered for the first time in the Riphean-Lower Vendian deposits, which have been recovered in 2002 by the Kel'tminskaya-1 deep parametric borehole in the Vychegda depression, the northeastern margin of the East European platform. The sampled interval of core section (4825-2347 m) consists of three units: the lower (depth range 4825-3995 m, 5 samples) and middle (depth range 3687-2961 m, 17 samples) carbonate successions overlain by sandstone-siltstone beds (depth range 2907-2347 m, 58 samples). Based on lithological criteria and/or composition of stromatolites, the carbonate successions are correlative with the Yshkemes and Vapol formations of the Upper Riphean of the Timan ridge succession, while the overlying, mostly siltstone succession was correlated with the Vychegda Formation of the southern Timan according to similarity in lithology and mineral composition. Microfossils found in 56 samples occur at 20 microphytological levels and represent different microbiotas. The Yshkemes and Vapol microbiotas of low diversity characterize six lower levels and represent one assemblage, while the diverse and abundant Vychegda microbiota typical of fourteen upper levels is divisible into three successive assemblages. The Vapol stromatolites Inzeria djejimii and Poludia polymorpha along with giant Chuaria and Navifusa present in the Yshkemes-Vapol assemblage suggest that their host deposits correspond to the upper Upper Riphean. The Vychegda assemblages, each of peculiar biostratigraphic specifics and unique in composition, consist of different morphotypes, primarily of large acanthomorphic acritarchs Cavaspina, Polyhedrosphaeridium, Cymatiosphaeridium, Asterocapsoides, and Tanarium, which are known in Scandinavia, Siberia, China, Australia, and India only in the Lower Vendian microbiotas of the Perthatataka type. The comprehensive microphytological characterization of the Lower Vendian in the Vychegda depression and earlier data on the Middle-Upper Riphean microbiotas from the adjacent Mezen syneclise enable a high-resolution biostratigraphic subdivision of the Riphean and Vendian successions in the vast region under consideration. © MAIK "Nauka/Interperiodica" 2006.
Keywords: ACANTHOMORPHIC ACRITARCHS; BIOSTRATIGRAPHY; EAST EUROPEAN PLATFORM; LOWER VENDIAN; PERTHATATAKA ASSEMBLAGE; Riphean; Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский; Докембрий::Протерозой::Рифей; Precambrian::Proterozoic::Riphean; Precambrian::Proterozoic::Neoproterozoic::Vendian